Biopesticides - towards increased consumer safety in the European Union - Czaja, Katarzyna; Góralczyk, Katarzyna; Struciński, Paweł; Hernik, Agnieszka; Korcz, Wojciech; Minorczyk, Maria; Łyczewska, Monika; Ludwicki, Jan K (Pest management science, 2015)
The introduction of new food safety regulations in the European Union has resulted in the withdrawal of many synthetic active substances used in plant protection products, in light of their potential or actual harmful effect on human and animal health, as well as on the environment. Alternatives to these compounds are being developed – naturally occurring pesticides, also referred to as biopesticides. The use of biopesticides in crop protection leads to decreased levels of pesticide residues in foods, and as a result to lower risk levels for the consumer. Biologically active agents defined as biopesticides are varied, and therefore application of the same environmental and consumer safety criteria to all of them is impossible. This presents serious complications in the approval of these pesticides as active plant protection products and in their registration. It needs to be stressed that, in the registration procedure of the European Union, biopesticides are subject to the same regulations as synthetic active substances. This situation has resulted in the need to introduce numerous new provisions in the legislation, as well as the preparation of new guidelines facilitating the registration of biopesticides. These activities aim to promote naturally originating pesticides. © 2014 Society of Chemical Industry